UJI KEMAMPUAN RIZOBAKTERI INDIGENOS SEBAGAI AGEN BIOKONTROL PENYAKIT ANTRAKNOSA PADA CABAI - Rahil Ade Rifqah (Ensiklopedia of Journal, 2018)
Anthracnose disease is a disease in chilli that can attack chili fruit in the field and post-harvest. Generally this disease control uses synthetic fungicide, with the development of science and technology found environmental friendly alternative controls to support sustainable agriculture by using rhizobacteria. This study aims to determine the ability of inhibit and effectiveness of rhizobacteria indigenous in inhibiting the development of Colletotrichum gloesporoides in vitro. This research using dual culture method on Tryptic Soya Agar media. The rizobacteria indigenous isolates tested RbLPK1-9, RbLPK1-9.1, RbTD1-3, RbTD1-8, RbTD1-8.1, RbAg1-5, RbGN3. The results showed that rhizobacteria isolate RBLPK1-9.1 had 50.60% inhibition 96.89% with effectivity, RbTD1-3 inhibition 50.66% with effectivity of 97.28%, RbTD1-8.1 inhibition 51.13% with effectiveness 98 , 72%, RbAg1-5 inhibition 45,96% with effectiveness 78,62%, RbGN3 inhibition 53,20% with effectiveness 107,00%, RbLpk1-9 inhibition 36,00% with effectivity 40,08%, RbTD1-8 inhibition of 28.23% with effectiveness of 9.73% and Control 25.73% with effectiveness 0%. This indicates that 5 isolates RBLPK1-9.1, RbTD1-3, RbTD1-8.1, RbAg1-5, RbGN3 are able to inhibit the development of C. gloeosporioides the cause of anthracnose disease in chili and can be used as biological agents.